Fables. [06], Homelands - Willingham, Bill (Fables, 2005)
Homelands follows Boy Blue on a mission of revenge as he uncovers the Adversary's true identity! Plus, the 2-part story of Jack's adventures in Hollywood and the one-shot story of Mowgli's return to Fabletown.